Options to Strengthen Disaster Risk Financing in Pakistan - World Bank (World Bank, Washington, DC, 2020)
The options presented in this paper were developed at the request of the Government of Pakistan (GoP) to contribute to the country's disaster resilience and overall sustainable development. They are in line with Pakistan@100: Shaping the Future which detailed essential elements of sustainable growth for Pakistan including with disaster risk financing among the